Multiple drivers of invasive lionfish culling efficiency in marine protected areas. Issue 11 (23rd September 2021) - Davis, Alexandra C. D.; Akins, Lad; Pollock, Clayton; Lundgren, Ian; Johnston, Michelle A.; Castillo, Bernard; Reale‐Munroe, Kynoch; McDonough, Vanessa; Moneysmith, Shelby; Green, Stephanie J.
Abstract: Designing effective local management for invasive species poses a major challenge for conservation, yet factors affecting intervention success and efficiency are rarely evaluated and incorporated into practice. We coordinated regional efforts by divers to cull invasive lionfish ( Pterois spp.) on 33 U.S. Atlantic, Gulf of Mexico, and Caribbean protected coral reefs from 2013 to 2019 and estimated removal efficiency and efficacy as a function of environmental and habitat conditions, invasion status, and personnel expertise. Highly experienced individuals culling during crepuscular periods (<2 hr from sunrise/sunset) are three times more efficient (in terms of minutes) than novice divers during midday, suggesting: (a) retention of experienced individuals is key for efficient programs, and (b) planning culls with personnel and time of day in mind increases the number of sites covered with the same effort. Lionfish behavior and habitat characteristics had little effect on removal efficiency and efficacy, but divers had higher capture success at reefs with higher lionfish densities. We suggest reefs with persistently <20 fish ha −1 as low priority, given that impacts to native fauna are unlikely and culling effectiveness declines to <50% below this level. Incorporating efficiency factors in spatial management planning along with density estimates derived from remotely sensed data can ensure limited resources for control are extended across a greater range of invaded habitats. Abstract : Many invasive species removal plans must now strive for suppressing densities rather than total eradication of the invasive species. Invasive lionfish in the Western Atlantic and Caribbean is such a species due to its widespread range and detrimental effects on native species. We found removal efficacy of invasive lionfish is determined by removal experience, density, and size of the lionfish as well as the time of day when removal are performed.